FAIRE SENS DES DONNÉES TERRITORIALES: Un exemple de technologie contributive. - Gilmozzi, Giacomo (Études Digitales, 2024)
The article focuses on the Urbanités Numériques En Jeux (UNEJ) project, which uses the video game Minetest to engage young people in reinventing their urban environment in Seine-Saint-Denis. This project is part of the Contributive Learning Territory (TAC) program and aims to promote citizen participation through school workshops, where students explore urban dynamics and propose territorial developments. By integrating geographic data and modeling technologies, UNEJ seeks to create spaces for democratic deliberation and to restore the residents' right to the city, while critiquing the standardizing logics of smart cities. The initiative highlights the importance of collaboration among different stakeholders to develop a sustainable and inclusive digital urbanity.